Cognitive Gains of Aerobic Exercise in Patients With Ischemic Cerebrovascular Disorder: A Systematic Review and Meta-Analysis - Shu, Yimei; He, Qing; Xie, Yi; Zhang, Wanrong; Zhai, Shuang; Wu, Ting (Frontiers in Cell and Developmental Biology, 2020)
Background: Cognitive impairment has become an important problem in cerebrovascular disorder survivors as disease related deaths have been significantly reduced. Aerobic exercise, the most prevalent mode of physical activity, positively contributes to cognition in both healthy population and people with cognitive impairment. However, studies on its associations with cognitive gains in patients with brain vascular disease showed mixed findings. Objective: To explore the cognitive effects of aerobic exercise on cerebrovascular disorder survivors and investigate the possible moderators on exercise benefits. Method: Randomized controlled trials investigating the effects of sole aerobic exercise on cognitive function in population with intracranial vascular disease compared to any control group who did not receive the intervention were enrolled in this systematic review and meta-analysis. Four online database (Pubmed, Cochrane Library, Embase and Web of Science) were searched. Results: The initial search returned 622 citations and ultimately 9 studies were included in the systematic review. Analysis of 6 studies showed the beneficial but not statistically significant impact of aerobic exercise on global cognitive function (0.13; 95% Cl -0.16 to 0.41; p = 0.37). Participants with cognitive impairment benefited more from this intervention (0.34; 95% Cl -0.01 to 0.69; p = 0.06) and moderate intensity might be the optimal choice(0.25; 95% Cl -0.04 to 0.54; p = 0.09). The program duration and initiation time after stroke occurrence did not predict better cognitive outcome. Aerobic exercise was not associated with improvement of processing speed and executive function, the two subdomains of cognitive function. Conclusions: Aerobic exercise may contribute to cognitive gains in survivors of cerebrovascular disorder, especially for population already with cognitive decline. Our findings support that the adoption of moderate intensity aerobic exercise couldimprove cognition in patients with cerebral vascular disease.